2021
DOI: 10.47059/alinteri/v36i2/ajas21114
|View full text |Cite
|
Sign up to set email alerts
|

Grounding of Design and Technology Parameters of Combined Coulter Furrow Opener of Precision Seed Drill

Abstract: A formation of a seedbed is an important step during seed sowing process. A quality of seedbed formation influences on seeds distribution along both a row and a depth and is triggering the opportunity to obtain early and even sprouts. The design of the furrow opener is the main element that has a direct impact on the qualitative formation of seedbed and technological parameters of coulter operation. During the research, there has been analyzed the modern construction of precision seed drills coulters and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Для реалізації наведених функцій виконання технологічного процесу нами був розроблений удосконалений сошник [32,33] який має комбінований клиновий наральник та щоки з додатковими елементами. Верхня більша частина наральника має робочу поверхню з гострим кутом входження в ґрунт, нижня менша частина та розміщена в задній частині п'ята, яка формує насіннєве ложе для рівномірного розміщення насіння по глибині, має робочу поверхню із тупим кутом входження ґрунт, причому в вертикальній площині обидві робочі поверхні наральника нахилені під кутом меншим кута тертя ґрунту по сталі (рис.…”
Section: обґрунтування функціонально-конструктивної моделі сошника дл...unclassified
See 1 more Smart Citation
“…Для реалізації наведених функцій виконання технологічного процесу нами був розроблений удосконалений сошник [32,33] який має комбінований клиновий наральник та щоки з додатковими елементами. Верхня більша частина наральника має робочу поверхню з гострим кутом входження в ґрунт, нижня менша частина та розміщена в задній частині п'ята, яка формує насіннєве ложе для рівномірного розміщення насіння по глибині, має робочу поверхню із тупим кутом входження ґрунт, причому в вертикальній площині обидві робочі поверхні наральника нахилені під кутом меншим кута тертя ґрунту по сталі (рис.…”
Section: обґрунтування функціонально-конструктивної моделі сошника дл...unclassified
“…Розрахунок кута входження в ґрунт нижньої частини наральника  , яка починає формування борозни виконується аналогічно і розглянутий в [33].…”
Section: рисунок 10 -схема взаємодії верхньої ґрунту з верхньою части...unclassified
“…The article [16] presents the materials of the study of the combined opener, which has sharp and obtuse angles of entry into the soil. The characteristics and parameters of the interaction of this opener with the soil are described.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Based on the analysis of the sources [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], it can be concluded that there are unresolved issues related to improving the uniformity of seed distribution by guiding elements in the openers.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%